The Use of Hyperbolic Figures of Speech (夸张) in Online Shopping Advertisements on Taobao: A Thematic Analysis of the Shift in Chinese Beauty Standards from ‘白瘦幼’ to ‘国潮美’. - Mar'atus S.B, Iffa; Subandi; Dzun Nun Septin Renda Rabbani; Rokhishotul Amaliyah; Ren Huiling; Lin Xinyue (E-Link Journal, 2025)
This study examines the use of hyperbole (夸张) in online shopping advertisements on the Taobao platform, with particular attention to how these expressions construct and represent the shift in Chinese beauty standards from the traditional ideal of 白瘦幼 (white, thin, youthful) to the emerging aesthetic trend 国潮美 (Chinese national-style beauty). Using a qualitative approach supported by multimodal discourse analysis of 40 Taobao advertisements (2020–2024), this study identifies key patterns in linguistic hyperbole, visual design, and embedded cultural meanings. The findings show that hyperbole in 白瘦幼-themed advertisements predominantly amplifies extreme and unrealistic beauty ideals. Meanwhile, hyperbole in 国潮美 themed advertisements emphasizes natural beauty, cultural symbolism, and national pride through expressions such as so stunning it leaves people breathless or instant oriental charm. These forms celebrate diversity and promote culturally rooted aesthetic values. Overall, the study demonstrates that hyperbole in Taobao advertisements serves not only as a persuasive rhetorical device but also as a cultural marker that reflects shifting beauty ideologies and growing cultural confidence in modern Chinese society. The research contributes to the fields of digital media linguistics, Chinese popular culture, and rhetorical strategies in online marketing